Penerapan Penggunaan Bahan Bakar Gas Elpiji 3 kg untuk Mesin Perontok Padi - Akhmadi, Amin Nur; Budi, Sigit Setijo; Fatkhurozzak, Faqih (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
This community service activity discusses efficiently converting fuel energy for rice thresher machines by replacing it with 3kg melon gas fuel. For the implementation of the Tri Dharma of Higher Education for Lecturers of the DIII Mechanical Engineering Study Program, Harapan Bersama Polytechnic. Providing knowledge and skills about using 3 kg LPG gas to replace gasoline fuel in diesel rice thresher machines. Improving the quality of human resources, especially for farmers. As an implementation of the MOU between the DIII Mechanical Engineering Study Program, Harapan Bersama Polytechnic, Tegal and the local village. The process of implementing PKM activities begins with preparation in the form of a survey of farmer partners to find out what problems are faced by farmers and then find solutions to the problems; from the solutions obtained, it turns out that farmer partners need training on the efficiency of using rice threshers that use 3Kg melon LPG gas fuel, so it is planned to be arranged for an activity on training the use of 3 kg gas as a fuel as a substitute for gasoline. With the presence of a gas converter tool, which can change gasoline fuel into 3kg of gas fuel, people are very happy because it can help provide fuel efficiency for diesel rice threshing machines so that they are not wasteful.